Dissecting mechanisms of brain aging by studying the intrinsic excitability of neurons - Rizzo, Valerio; Richman, Jeffrey; Puthanveettil, Sathyanarayanan V. (Frontiers in Aging Neuroscience, 2015)
Several studies using vertebrate and invertebrate animal models have shown aging associated changes in brain function. Importantly, changes in soma size, loss or regression of dendrites and dendritic spines and alterations in the expression of neurotransmitter receptors in specific neurons were described. Despite this understanding, how aging impacts intrinsic properties of individual neurons or circuits that govern a defined behavior is yet to be determined. Here we discuss current understanding of specific electrophysiological changes in individual neurons and circuits during aging.